Boron isotope fractionation during the formation of amorphous calcium carbonates and their transformation to Mg-calcite and aragonite. (15th December 2021) - Mavromatis, V.; Purgstaller, B.; Louvat, P.; Faure, L.; Montouillout, V.; Gaillardet, J.; Schott, J.
Abstract: The non-classical crystallization pathway of carbonate minerals proceeds through the initial formation of an amorphous precursor phase and commonly takes place during biomineralization. Although the isotopic composition of marine calcifiers is often used to reconstruct paleo-environmental conditions, the impact of the crystallization pathway followed by these organisms on the isotope composition of their skeletons has rarely been quantified. This study presents the first examination of B partitioning and isotope fractionation during CaCO3 formation via an amorphous calcium carbonate phase, which provides new insights into the incorporation of B into marine calcite and aragonite that form via this route. Boron concentrations and isotope compositions of the fluids and the formed solids were characterized during the course of experiments that lasted two years and were performed at 25 °C under controlled pH conditions. The results suggest that during Mg-ACC formation, B distribution coefficients are 1.5–4 orders of magnitude higher than those reported earlier in the literature for calcite and aragonite. Additionally, B isotope fractionation during Mg-ACC formation is strongly affected by the continuous exchange of solutes between the nanoporous solid phase and the bulk fluid. The isotope composition of the transient amorphous phase is not inherited in the crystalline carbonate mineral phase that ultimately forms, because crystallization proceeds via a continuous dissolution/re-precipitation process and/or chemical/isotope exchange between the solid surface and the fluid. Interestingly, the isotope fractionation between the fluid and the final crystalline products is different from those achieved in earlier studies where mineral growth proceeded via the standard mechanism of ion-by-ion addition of solutes to advancing steps. The B isotope fractionations measured in this study are in good agreement with results of equilibrium first principle calculations for calcite and aragonite (Balan et al., 2018) except in the case of calcite formed at pH = 8.9, suggesting that changes in aqueous speciation (i.e. increase of NaB(OH)4 ° and CO3 2− concentrations) may be responsible for slight changes of the calcite BO4 environment and isotope composition. It is expected that this study will help to better decipher the mechanisms controlling B isotope fractionation during the non-classical growth of calcium carbonates involving the formation of transient amorphous precursors.